2010
DOI: 10.1007/s12032-010-9732-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, pathological and oncological relevance of Gb3Cer receptor

Abstract: Glycosphingolipids are amphipathic molecules composed of hydrophilic oligosaccharide chain and a hydrophobic ceramide part, located primarily in the membrane microdomains of animal cells. Their oligosaccharide chains make them excellent candidates for the cell surface recognition molecules. Natural glycosphingolipid, globotriaosylceramide (Gal α1-4, Gal β1-4, Glc β1-1, ceramide), is also called CD77 and its expression was previously associated with proliferating centroblasts undergoing somatic hypermutation, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 113 publications
(108 reference statements)
0
16
0
Order By: Relevance
“…Third, Gb 3 and verotoxin internalization and intracellular traffic provide a probe of the molecular basis of retrograde transport to the ER (58). Fourth, Gb 3 is up-regulated in many human tumor cells, and thus verotoxin itself (59, 60, 61) or the B subunit pentamer coupled to cytotoxic drugs (62,63) offers new antineoplastic approaches (64). In this area also, as with HUS, endothelial cells within the neovasculature express Gb 3 and are VTsensitive (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Third, Gb 3 and verotoxin internalization and intracellular traffic provide a probe of the molecular basis of retrograde transport to the ER (58). Fourth, Gb 3 is up-regulated in many human tumor cells, and thus verotoxin itself (59, 60, 61) or the B subunit pentamer coupled to cytotoxic drugs (62,63) offers new antineoplastic approaches (64). In this area also, as with HUS, endothelial cells within the neovasculature express Gb 3 and are VTsensitive (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the carbohydrate-binding pentameric B-subunit of E. coli verotoxin causes apoptosis in susceptible endothelial cells, such as the Eahy.926 hybridoma cell line, upon binding to the GbO3 glycolipid receptor (64,65), which makes the interaction of GbO3 with endogenous and exogenous ligands a potential target for therapies. The availability of the SadP with its distinct and well characterized Gal␣1-4Gal binding specificity could be a useful tool in studies aiming at these goals.…”
Section: Discussionmentioning
confidence: 99%
“…Gb3/CD77 receptors are abundant in various host tissues including human and pig small intestine in the precursor (Gb3/CD77) or mature form (globotetraosylceramide Gb4) [13, 14]. Furthermore, Gb3/CD77 is a receptor for adhesin-mediated binding to host tissues of multiple human pathogens and serves as receptor for bacterial toxins (Shiga toxins, Stx) [15]. …”
Section: Introductionmentioning
confidence: 99%